Perlindungan Hukum bagi Anak di Bawah Umur dari Predator Seksual Online di Platform Media Sosial - Kelvin Martino Mantinia (Jurnal Hukum Lex Generalis, 2025)
The development of digital technology has significantly impacted children and adolescents, with 75.5% of internet users aged 10–17 actively engaging on social media. Despite its benefits, digitalization has also triggered risks of online child sexual exploitation (OCSEA). This study employs a normative juridical method with a qualitative approach to analyze crime patterns and the effectiveness of legal protection in Indonesia. Findings show that older perpetrators receive heavier criminal sanctions, while restorative justice may be applied to peers or younger offenders. Synergy between the state, society, and digital platforms is essential to create a safe online environment for children.